RELIGIOUS ATTITUDES OF CHACH OASIS NOMADS DURING THE PERIOD TURKIC KHAGANATE - Rahmanali Muradaliyev; Tuba Tombuloğlu (Türk Kültürü ve Hacı Bektaş Velî Araştırma Dergisi, 2025)
Based on ancient sources, Turkologists have highlighted the shamanic nature of the religion of the early settled nomadic Turks. In later periods, researchers identified elements such as animism and totemism in the religious beliefs of the settled nomadic Turks, who had adopted only the elements of shamanism. In Central Asia, however, the situation presents a different reality when compared to the Eurasian steppe region in the early Middle Ages. Zoroastrianism, the dominant religion of that period, played an important role in this region. Additionally, various local cults were widespread in the early Middle Ages, with the cult of ancestor spirits being particularly prominent. Related beliefs, such as the death and resurrection of nature, as well as Buddhism, Manichaeism, and Christianity, also had an influence.In the Chach (Tashkent) region of Central Asia, differences in religious views have been observed since ancient times. By the early Middle Ages, this diversity had further increased. During this period, Zoroastrianism began to spread, and its symbols became clearly visible in funeral ceremonies. In almost every part of the Chach (Tashkent) region, funeral rites were conducted according to the ideological traditions of this religion. However, it is also a well-known fact that local traditions were enriched by new influences from the world of settled nomadic Turks.Moreover, the tradition of burying the dead with horses has existed in Uzbekistan since the 6th to 8th centuries, that is, since the period of the Turkic Khaganate. The ancient Turks considered the horse to be a creature that could speak and fly. The horse, which held an important place in daily life, later became a sacred object. Monuments to the horse totem have also been preserved in Uzbek traditions. In more recent times, when a wealthy person died, close family members and relatives would throw the deceased’s clothes onto a horse, walk around the animal, and recall the deceased's good qualities and deeds. Many families in the Fergana Valley, associated with the Kipchaks, were linked to the horse totem. The Kipchak families living in the region viewed the horse as a legendary breed and held it in high esteem. However, over time, the horse’s function changed, and it began to be sacrificed in funeral ceremonies, symbolically associated with the deceased.This study has been prepared to provide new insights into some forgotten traditions of the Chach (Tashkent) region during the period of the Turkic Khaganate.